Investigating the antimicrobial and anti-inflammatory effects of Lactobacillus and Bifidobacterium spp. on cariogenic and periodontitis pathogens - Mahdizade Ari, Marzie; Mirkalantari, Shiva; Darban-Sarokhalil, Davood; Darbandi, Atieh; Razavi, Shabnam; Talebi, Malihe (Frontiers in Microbiology, 2024)
The use of probiotics is emerging as an innovative approach to managing oral health issues and mediating the immune system. The current study assessed the in vitro impacts of non-orally isolated probiotics on periodontitis and tooth decay pathogens.Methods: Briefly, the persistence of probiotics in exposure to oral cavity enzymes, hydrogen peroxide, and saliva samples was examined. It was also investigated the biofilm formation and aggregation ability of probiotics, the adherence of probiotics in human gingival fibroblast cell (HGFC) lines and molar teeth samples, and the potential of probiotics to co-aggregate with oral pathogens. Additionally, the current study evaluated the effects of live probiotics on virulence gene expression, biofilm production of main oral pathogens, and changes in inflammation markers.The probiotics remained alive when exposed to enzymes in the oral cavity, hydrogen peroxide, and saliva at baseline, 1, 3 and 5 hours after incubation at 37 °C (p value < 0.05).Probiotics demonstrated to produce biofilm and aggregation, as well as adherence to HGFCs and maxillary molars (p value > 0.05). They showed significant co-aggregation with oral pathogens, which were recorded as 65.57% for B. bifidum 1001 with S. mutans, 50.06% for B. bifidum 1005 with P. gingivalis, 35.6% for L. plantarum 156 with F. nucleatum, and 18.7% for B. longum 1044 with A. actinomycetemcomitans after 8 hours of incubation. A balance between pro-inflammatory and anti-inflammatory cytokines, along with inhibition of biofilm formation and changes in virulence gene transcripts, were observed. However, most of these changes were not statistically significant (p value > 0.05).Conclusions: This study demonstrated the direct link between adhesiveness, aggregation, and biofilm formation with probiotic antibacterial activity. In addition to the careful selection of suitable probiotic strains, the concentration and origin of probiotic isolates should be considered.